Caminhos que estruturam cidades: redes técnicas de transporte sobre trilhos e a conformação intra-urbana de Natal - Medeiros, Gabriel Leopoldino Paulo de (2011)
The railroad, from 1870 and on, becomes an usual complaining in the press s and politician elite s speeches, especially because of Natal s geographic isolation. The implantation of two railroads in the capital territory Estrada de Ferro de Natal a Nova Cruz, afterwards part of Great Western Railway Company network, and Estrada de Ferro Central do Rio Grande do Norte had serious implications in the urban environment. While railroad s structures were already consolidated, other transportation mechanisms were being implanted in the first decades of the 20th century, such as trams lines, which, by the way, was a transport modal that also used rails as a dislocation meaning. Considering these questions, we may ask: how come railroads and tramways demands, roads and buildings had influenced the internal organization of Natal? We work with the general hypothesis that the influence of technical networks, composed by tramways and railroads, over Natal s urban space happened in a diversified way, sometimes consolidating social aspects in certain areas, sometimes improving the occupation of others. The impact over the city s territory also happens in a diversified way between the buildings/railroad s complexes and the pathways. The different scale of the train in comparison to the trams velocity, size, noise level, flow, among others is also a cause to the different consequences in urban environment. The main objective of this work is to understand the role of circulation technical networks in the construction process of urban space in Natal, as a way to contribute to the urban historiography about the subject. The time frame adopted, between 1881 and 1937, marks the time path of railroads and tramways in Rio Grande do Norte: 1881 is the year of railroad s first section inauguration from Natal to São José do Mipibu as well of the railroad complex in the Republic Square in Natal; the year of 1937 marks the beginning of tramways declination process in the city. At this time railroads and tramways had to face more intensively the competition of motor vehicles. The theory reference adopted is based on concepts and analysis of authors, such as Flávio Villaça and Roberto Lobato Corrêa references to the concepts of urban structure , localization and accessibility and Gabriel Dupuy to explain the concept of urban technical networks . These references reveal the conflict of different realities in the urban universe interests and values which is an important factor about the construction of urban space. The information sources used were from two distinctive natures: primary, journals of the time studied and official government reports, and secondary, based on other works about the subject. It was also used by this study iconographic source, especially images from the data base of the research group História da Cidade, do Território e do Urbanismo .